This preview shows page 1. Sign up to view the full content.
Unformatted text preview: (Section 1.6: Combining Functions) 1.6.13 () • We then need f to apply the square root operation. We will let f u = u . () The use of u is more helpful in calculus, but f x = x is also () acceptable. However, f u = x is not acceptable. () () Possible Answer: Let g x = 3x + 1 and f u = u . x () g: g x = 3x + 1 f: 3x + 1, our u () fu= u g ( x) 3x + 1
f g ( x) fg There are infinitely many possible answers.
For example, we could let g x = 3x and f u = u + 1 . () x g: () g x = 3x 3x , our u
g ( x) fg
§ () () f: f u = u +1 3x + 1
f g ( x) ...
View Full Document
This document was uploaded on 12/29/2011.
- Spring '09